Alliance Constellations: A Social Exchange Perspective - Das, T. K.; Teng, Bing‐Sheng (Academy of Management Review, 2002)
We develop a social exchange perspective of alliance constellations, emphasizing the role of generalized exchanges. We then discuss three social control mechanisms for mitigating the unique difficulties of managing constellations, and we conclude by proposing a typology of constellations based on the dimensions of exchange horizon and type of generalized reciprocity. The perspective presented here contributes not only to research on alliances but also to the larger body of literature on generalized social exchange processes, which has traditionally been centered on interpersonal relations.